THE USE OF THE PERSONAL NARRATIVE IN SOCIAL WORK WITH THE ELDERLY - Howes, Francis (Social Work/Maatskaplike Werk, 2006)
Reminiscence and life review have always been regarded as integral parts of the aging process. In the past, however, a stereotypical view of the aged often prevailed. According to Kaminsky (1978:19), this view entails that “…we view them as categories and not as individuals, when the meaning of their characteristic behavior is already fixed in our minds, without our having given them the kind of finely tuned hearing which is vital to understand another human being.” Stereotyping the elderly means that reminiscence and life review are dismissed derogatively as intellectual decline; living in the past; approaching dementia or second childhood; or as symptoms of loneliness; lack of new experiences or clinging to a previous identity (Lewis & Butler, 1974; Kaminsky, 1978). Social workers and other professionals working with the elderly have therefore frequently dismissed these phenomena as meaningless, boring, time consuming and indicative of an irreversible condition.